EVALUASI PERENCANAAN SALURAN DRAINASE JALAN GURU HAMZAH KOTA BUKITTINGGI - Masril, Masril (Ensiklopedia of Journal, 2026)
Evaluation of drainage channel planning is an important process in the management of urban drainage systems. The purpose of this evaluation is to determine whether the existing drainage channels have been well planned and constructed, so that they can function effectively and efficiently in addressing the problem of waterlogging and flooding. Evaluation of drainage channel planning includes analysis of the design, construction, and operation of drainage channels, as well as identification of problems and recommendations for improvement. Thus, evaluation of drainage channel planning can help improve the performance of the drainage system and reduce the risk of waterlogging and flooding in urban areas. This study also analyzes the performance of the drainage system on Jalan Guru Hamzah, Bukittinggi City., that the drainage channel on Guru Hamzah. For this reason, a cross-sectional channel with a size of 1.20 x 1.20 m is planned, so that the planned channel discharge is obtained with a Q of 2.71 m3 / sec. From the results of the analysis carried out, it can be concluded that the planned channel can accommodate the design flood discharge for the 2nd, 5th, 10th and 25th year return periods, with a ratio of Q planned channel > Q return period.Keywords: drainage planning, waste water discharge, planned flood discharge, rainfall